Human Ecological Roles and Tasks in The Quran PERAN DAN TUGAS EKOLOGIS MANUSIA DALAM AL-QUR’AN - Karunia, M. Octa Puji; Kharirotul Badriyah (Aqwal: Journal of Qur'an and Hadis Studies, 2022)
Humans are people who have the authority to manage the earth. They should realize that protecting the environment is a part of several obligations to God. Unfortunately, some people assume that protecting the environment is not a part of worship like other mahdzhah’s worship. This assumption has a fatal impact on the balance of the environment, which it from year to year experiences significant environmental degradations. In other words, humans only want to cultivate the earth and then take advantages of it without wanting to make improvements or preserving the environment. This paper will discuss about the role and ecological tasks of humans which its patterns can be read in the verses of the Koran. The article focuses on discussing the verses with the keywords khalifah, khalaif, abdullah, and ista’amara. The method applied in this paper is the thematic interpretation method, in which the verses with the terms above become the main study. The verses will be analyzed from a historical perspective and then will be contextualized. The result of this research is producing relevant contextualizations. The conclusion of the ecological roles and ecological tasks of humans in the Quran is humans have two roles, both are khalifah and abdullah. The ecological task of humans is to prosper the earth together not individually.